Acute abdomen as a side-effect of sodium–glucose co-transporter 2 inhibitors in diabetic patients. Issue 12 (13th November 2021) - Kietaibl, Antonia-Therese; Fasching, Peter; Glaser, Karl; Petter-Puchner, Alexander H
Abstract : This multidisciplinary article gives a brief overview of the literature about sodium–glucose co-transporter 2 inhibitor-induced ketoacidosis in the surgical and perioperative context.